Nursing students’ perspectives on the operator portraying the patient in simulation - Reierson, Inger Åse; Haukedal, Thor Arne; Husebø, Sissel Iren Eikeland; Solli, Hilde (Teaching and learning in nursing, 2024)
•Knowledge of the simulator operator role has been limited to technical orientation.•Portraying the high-fidelity patient in simulation is a complex pedagogical role.•The operator's pedagogical expertise is crucial for enhancing students’ learning. The simulation operator plays an important role in portraying the patient when using high-fidelity simulators. However, knowledge of the simulation operator's pedagogical role in simulation scenarios, from the perspective of nursing students, is limited. To explore nursing students' perspectives on the simulation operator role. The study was conducted at a university in Norway. An exploratory, descriptive design with a qualitative approach was employed. Participants comprised 34 nursing students. Data were collected via focus groups and analyzed using qualitative content analysis. One main category, creating an attuned learning path on the fly, emerged, alongside three associated subcategories: triggering student alertness, providing dynamic feedback, and mastering technical challenges. Findings from this study suggest that simulation-based learning experience should include the operator's role as a critical educator role in nursing education. The efficacy hinged on the simulation operator's ability to merge and apply subject-matter expertise and pedagogical competencies to guide students further within their Zone of Proximal Development. Further research on the operator's multifaceted pedagogical role would help develop evidence-based guidelines for this pivotal function.